Preaching and pastoral care in late antique Gaul: The Eusebius Gallicanus sermon collection - Bailey, Lisa Kaaren; Princeton University (2004)
This dissertation argues that pastoral care was one of the foundations for the success of the late antique Church in integrating itself into the society and culture of Western Europe. Day-to-day interactions between clergy and laity determined the form of that Church and established what it could expect of its members. Sermons are one of the few surviving witnesses to late antique pastoral care and were a central vehicle of it. They reveal the pastor at work. As yet, scholars have concentrated on the words of a relatively limited number of well-known preachers, but a vast body of anonymous and paradigmatic sermon texts also survive, and these cast a different light on late antique pastoral care.
This work focuses on the evidence of the Eusebius Gallicanus, an anonymous collection of sermons from fifth-century Gaul. These sermons were compiled into a preaching resource in the sixth century and enjoyed a remarkable, but generally unrecognised popularity and influence in the early middle ages. They illustrate how pastors built up and sustained the bonds of Christian community, explained a complicated faith to their congregations and maintained consensus in the face of sin through systems of penance and expiation. The authors of the sermons extended models of monastic community into lay contexts and expected of their congregations a commitment not to ascetic behaviour, but to individual responsibility for salvation and to the good of the group. When the styles of pastoral care found in the Eusebius Gallicanus sermons are compared with those of roughly contemporary preachers it becomes clear that the late antique Church was not a monolith.
The dissipation of central authority in late antiquity meant that clergy were increasingly forced to fall back upon their own resources, and led to localised, varied responses to the challenges of the time. Preachers drew on a common Christian heritage to create different styles of pastoral care. The flexibility which resulted subsequently frustrated reformers, but also meant that the Church could adapt to the demands of different cultures and different times. The strategies of late antique pastors helped make 'Christendom' possible
(UnM)AAI3119373
Adviser: Peter Brown.
Source: Dissertation Abstracts International, Volume: 65-01, Section: A, page: 0253.
Thesis (Ph.D.)--Princeton University, 2004.
Microfiche.
Keywords: History, European; History, Medieval